Kalyptorhynchia (Platyhelminthes: Rhabdocoela) from KwaZulu-Natal (South Africa), with the description of six new species - Willems, Wim R.; Reygel, Patrick; Steenkiste, Niels Van; Tessens, Bart; Artois, Tom J. (Zootaxa, 2017)
Fifteen species of kalyptorhynch flatworms, twelve of them eukalyptorhynchs and three schizorhynchs, are reported from the KwaZulu-Natal coast in South Africa. Six species are new to science, five of which belong to Eukalyptorhynchia, the remaining one to Schizorhynchia. One of the new eukalyptorhynch species, Uncinorhynchus linusi n. sp., belongs to the taxon Gnathorhynchidae Meixner, 1929 and can be distinguished from other species of Uncinorhynchus Karling, 1947 based on the detailed structure of the proboscis hooks and the hard part in the male genital system. Two other species are members of the Koinocystididae Meixner, 1924. Itaipusa sbui n. sp. is characterised by an armed cirrus with two transversal bands of lamellar spines and by the detailed structure of the female genital system. The other new koinocystidid cannot be placed in any existing taxon and therefore a new genus is erected: Bhambathorhynchus abursalis n. gen. n. sp. It is characterised by the presence of two bent hooks in the male system, each one connected to a muscular bulb, and by the absence of a copulatory bursa. The remaining two new species of Eukalyptorhynchia, Lagenopolycystis mandelai n. sp. and Phonorhynchoides gondwanae n. sp., are members of the taxon Polycystididae Graff, 1905 and can be distinguished from their respective congeners by the detailed structure of their hard parts in the male genital system. The latter species also occurs on the Indian subcontinent. The discussion on the phylogenetic position of the new species of Phonorhynchoides leads to the formal split of this non-monophyletic genus into two taxa: Phonorhynchoides Beklemischev, 1927 and Phonorhynchopsis n. gen. The sixth and last new species, Baltoplana cupressus n. sp., is a member of the taxon Cheliplanidae Schilke, 1970 (Schizorhynchia) and combines an armed cirrus with a single accessory cirrus in the copulatory organ. For two more species, Prognathorhynchus spec. and Carcharodorhynchus spec., the available material is inadequate for a formal description, but they are mentioned and illustrated to allow future recognition. Six known species, Pocillorhynchus spiroductus Schockaert, 1982, Duplacrorhynchus heyleni Artois & Schockaert, 1999, Gyratrix hermaphroditus Ehrenberg, 1831, Paulodora contortoides Artois & Tessens, 2008, P. drepanophora Artois & Tessens, 2008 and Cheliplana pileola Jouk & De Vocht, 1989 are reported from South Africa for the first time and additional remarks on their morphology are given. An additional species, Brachyrhynchoides oosterlyncki (Willems, Reygel & Artois, 2013) Willems, Reygel & Artois, 2013 was recently described from South Africa and India (see Artois et al., 2013b, 2013c), and is mentioned here for the sake of completeness.